PEDAGOGICAL COMPETENCY OF TEACHERS OF PROFESSIONAL EDUCATIONAL INSTITUTIONS: CHALLENGES AND ASSESSMENT - Sergeeva, Marina; Alexandrova, Alexandrova; Mukhin, Mikhail; Oreshkina, Anna; Lukashenko, Dmitry (Revista Inclusiones, 2020)
The production capacity of a state is a key condition for the sustainable economic and social development. The competence and skill level of employees in any position, from cashier to federal official, affects not only labor efficiency, but also the speed of progress in the economic field and, finally, the overall competitiveness of Russia in the context of international market relations. The contributory factors that determine the level of competitiveness of the state economy include the quality of workforce training, directly related to the integration of the economic sphere (one of the four basic spheres, along with political, social and spiritual) with the educational sector. Moreover, from the point of view of the overwhelming majority of Russian education researchers, nowadays, we face serious challenges with the training of highly skilled workers. Managers are forced to bring their employees to the necessary professional level through special in-service courses and programs. An effective solution to the problems of continuing professional development is facilitated by the promotion of employees up the career ladder. It can be described as a gradual advancement of professionals in the field of industrial, scientific, creative or any other constructive activity from the basic qualification level to the highest, or, in other words, as a career development of a particular individual, taking into account his/her mental, psychological, professional and other resources.